Mining Method Optimization of Gently Inclined and Soft Broken Complex Ore Body Based on AHP and TOPSIS: Taking Miao-Ling Gold Mine of China as an Example - Qinqiang Guo (MDPI AG, 2021)
The gently inclined thin to medium thickness ore body under a weak rock stratum is one of the typical difficult bodies to mine. In order to solve the fuzziness, randomness, and uncertainty in the process of mining method optimization for such ore bodies, a multi-level, multi-factor, multi-objective, and multi-index comprehensive evaluation system involving technology, economy, construction, and safety was constructed by combining the analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS). Taking the Miao-ling gold mine in China as an example, the AHP-TOPSIS comprehensive decision model of mining method optimization is established, the comprehensive superiority degrees of the four mining schemes are 67.57%, 45.07%, 56.07%, and 31.63%, and the upward horizontal drift backfill mining method is determined as the optimal scheme. The method is verified in the actual production of the mine, which not only ensures the safe production of the mine, but also achieves better technical and economic effects. The research results provide a reference for the optimization of mining methods for gently inclined and soft broken complex ore bodies at home and abroad.